Transforming Payment Security: AI-Driven Solutions for Enterprise Fraud Prevention - Nagaraju Velur (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines PayPal’s innovative implementation of artificial intelligence and behavioral analytics to revolutionize enterprise security and fraud prevention in digital payment systems. As a global payment platform processing millions of daily transactions across hundreds of markets, PayPal faced unique challenges balancing robust security with frictionless user experience. The article explores how PayPal transformed its security architecture from traditional rule-based systems to an intelligent, adaptive framework capable of evolving alongside emerging threats. The article details the multi-layered machine learning infrastructure, comprehensive data integration strategy, and sophisticated behavioral analytics that form the foundation of PayPal’s approach. The article analyzes the real-time anomaly detection framework that evaluates user activities as they occur, the technical approaches to minimize false positives while maintaining strong security, and the quantifiable business outcomes achieved through this implementation. Finally, the article examines future technological directions and broader implications for enterprise security frameworks across the financial services industry, highlighting how PayPal’s balanced approach has redefined what’s possible in payment security.